1996
DOI: 10.1159/000174096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renal Ischemia on Organic Anion and Cation Transport in Rabbit Proximal Tubule

Abstract: The uptake of organic anion, ρ-aminohippurate (PAH), and organic cation, tetraethylammonium (TEA), was measured in cortical slices and plasma membrane vesicles isolated from the proximal tubule of ischemic rabbit kidneys. The uptake of PAH or TEA in cortical slices increased after 30 or 60 min of ischemia. When the kidneys were reperfused for 30 min, the uptake of organic ions returned to control levels. When ischemic (60 min) slices were preincubated for 120 min in an oxygenated medium, the stimulatory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Secretion and reabsorption of organic cations have been described in renal proximal tubules but may also occur in distal tubules or collecting ducts (1,2,6,24). The mechanisms mediating tubular secretion have been intensively studied in various experimental preparations from rabbit kidney, including perfused (9,24,38) and nonperfused (5,10,15,38) tubules, apical (12,26,29,44,45) and basolateral (28,39,44) membrane vesicles, and isolated tissue slices (21). Results from these studies identified two distinct functional classes of organic cation transporter (OCT): one localized at the basolateral membrane that is stimulated by the inside-negative membrane potential of proximal cells and the other at the brush-border membrane that is stimulated by an inwardly directed proton gradient (35).…”
mentioning
confidence: 99%
“…Secretion and reabsorption of organic cations have been described in renal proximal tubules but may also occur in distal tubules or collecting ducts (1,2,6,24). The mechanisms mediating tubular secretion have been intensively studied in various experimental preparations from rabbit kidney, including perfused (9,24,38) and nonperfused (5,10,15,38) tubules, apical (12,26,29,44,45) and basolateral (28,39,44) membrane vesicles, and isolated tissue slices (21). Results from these studies identified two distinct functional classes of organic cation transporter (OCT): one localized at the basolateral membrane that is stimulated by the inside-negative membrane potential of proximal cells and the other at the brush-border membrane that is stimulated by an inwardly directed proton gradient (35).…”
mentioning
confidence: 99%